The Mediating Role of Alexithymia in the Relationship Between Perceived Parental Rejection and Somatization - Zeynep Haktanır; Işıl Çoklar Okutkan (Psikoloji Çalışmaları)
Somatic complaints are a prevalent psychological problem many adults experience. Alexithymia is characterized by difficulty identifying and expressing feelings and is widely considered to be a strong predictor of somatic complaints. Previous studies have indicated adverse childhood experiences to be associated with alexithymia and somatization. In this regard, interpersonal acceptance-rejection theory provides a comprehensive perspective that focuses on the effects the caregiver-infancy relationship that is established in the early years of life has on personality characteristics and psychological well-being. The aim of the current research is to examine the effects of perceived parental rejection on alexithymia and somatic complaints in adults using two separate models. The study will analyze the effect of maternal rejection while controlling for the effect of paternal rejection, as well as the effect of paternal rejection while controlling for the effect of maternal rejection. The research also intends to contribute to the literature by investigating the mediating roles the three sub-dimensions of alexithymia has on these relationships. Data were collected online from 328 participants in Türkiye, of whom 224 are women and 104 are men. All participants filled out a socio-demographic form, the Somatization Subscale of the Symptom Checklist 90-R (SCL-90-R; Derogatis, 1977), the mother and father versions of the Adult Parental Acceptance-Rejection Questionnaire (Rohner & Khaleque, 2005), and the Toronto Alexithymia Scale (TAS-20; Bagby et al., 1994). The results reveal perceived maternal rejection to predict somatization as well as the TAS-20 subscales of difficulty identifying emotions and difficulty expressing emotions when controlling for the effect of perceived paternal rejection. In addition, the TAS-20 component of difficulty identifying emotions was found to mediate the relationship between perceived maternal rejection and somatization. Perceived paternal rejection had no statistically significant effects on somatization or the sub-dimensions of alexithymia when controlling for the effect of perceived maternal rejection. The results confirm previous research regarding the relationship between somatization and alexithymia. Additionally, this research expands on the results in the literature by emphasizing how perceived parental rejection from the mother predicts somatization through the sub-dimensions of alexithymia. The findings have been evaluated in light of the literature, with the study’s strengths, limitations, practical implications, and recommendations for future research also being discussed.